Prehospital dyspnoea - Kauppi, Wivica (University of Borås, 2023)
Observational study, which was based on retrospective journal review. The samples consisted of all ambulance missions (n=7260) that were classified as ESS 04 (dyspnoea as the main symptom) by ambulance clinicians during the year 2017 in two areas in southwestern Sweden, which included 16 ambulance stations. After a manual review of ambulance records and hospital records, 908 patients were excluded (reason: age < 16 years, missing social security number, ambulance transports to hospitals outside included areas, duplicate ambulance records, insufficient documentation, incorrect ESS code and secondary transports). This meant that 6354 patients were finally included.

Observationsstudier vilka baserades på retrospektiv journalgranskning. Urvalet bestod av samtliga ambulansuppdrag (n=7260) som klassificerats som ESS 04 (andnöd som huvudsymtom) av vårdare i ambulans under år 2017 i två upptagningsområden i sydvästra Sverige, vilket inkluderade 16
ambulansstationer. Efter en manuell granskning av ambulansjournaler och sjukhusjournaler exkluderades 908 patienter (orsak: ålder < 16 år, personnummer saknades, ambulanstransporter till sjukhus utanför inkluderade upptagningsområden, dubbla ambulansjournaler, bristfällig dokumentation, felaktig ESS kod samt sekundärtransporter). Detta medförde att 6354 patienter slutligen inkluderades.
Prehospital andnöd
Keywords: Dyspnea; Andnöd; AMBULANCE SERVICES; AMBULANSVÄSEN; Ambulances; Ambulanser; Emergency Medical Services; Akutsjukvård; Dyspnoea; Dyspné; Dyspnoea; Dyspnoea; Ambulance; Ambulans; Breathing difficulties; Andnöd; Prehospital; Prehospital; Prehospital emergency care; Prehospital akutsjuvård; Other Clinical Medicine; Annan klinisk medicin; Signs and symptoms; pathological conditions; Tecken och symtom; patologiska tillstånd